Preconditionos for successful education of children with autism spectrum disorder at primary general school: experience of parents - Raudeliūnaitė, Rita; Gudžinskienė, Vida (Special Education, 2022)
Children with disabilities, as all other children, have a right to be educated in the general education system and receive quality education, yet in practice, in other countries and Lithuania, a number of shortcomings can be observed in this area. It is noteworthy that significant challenges to inclusive education are raised by the education of children with ASD. Children with ASD are more sensitive to the environment surrounding them. It is influenced by social interactions, communication difficulties, repetitive, stereotyped behaviour, interests of children with ASD, as well as the lack of the readiness of the child’s environment to respond to his/her individual needs. The presence of children with ASD at a school of general education by no means guarantees their inclusion, it is important to create appropriate conditions for them to participate in the educational process meaningfully and actively, to engage them in joint activities with their peers, to feel that they are the part of the community of their classroom, their school and to reach goals and results in line with their abilities. Although recently scientists increasingly devote more of their attention to the education of children with ASD, however, there is lack of research revealing the preconditions of their successful education at schools of general education. Therefore, it is relevant to reveal real experience of the inclusion of such children into educational system. The article reveals the preconditions of the successful education of children with ASD at a primary school of general education based on the experience of parents. A qualitative study, while using a semi-structered interview method, was chosen. Six parents of children with ASD, whose child attends a primary school of general education, participated in the research. The obtained data were analysed while using a qualitative content analysis method while adhering to an inductive logic, which is based on the study data, when creating topics. The study established that the preconditions of the successful education of children with ASD at a primary school of general education should be associated with the acceptance of the disability of the child by his/her parents and their openness, having detected ASD in their child, adequate preparedness of the school to receive children with ASD, the readiness of the child to attend school, the cooperation between parents and the school, the focusing on the child’s adaptation at his/her school and the creation of a favourable educational environment in the classroom. The acceptance of the disability of the child by his/her parents and their openness, having detected ASD in their child, should be associated with the ability of parents to accept information presented by specialists and to consult with them and their interest in the education of a child with ASD. The acceptance of the disability of the child by his/her parents and their openness should also be associated with the need of psychological assistance in parents and its obtainment both from specialists and when joining the groups of parents rearing children with ASD. In addition, it is important that parents do not conceal the disability of their child from the school, because the school, while being aware of individual educational needs of the child, is able to respond to them and to provide the necessary assistance to the child. The successful education of children with ASD is also guaranteed by the preparedness of the school to receive children with ASD which encompasses the openness of the school community to the inclusion of children with ASD, sufficient resources of the specialists of educational assistance, their competence to provide assistance to a child with ASD, teachers, parents and a positive attitude of teachers and their competence to educate children with ASD, as well as teamwork and cooperation with other institutions coupled with their assistance, consultations and the sharing of good practice. In addition, there arises a need for intervisions and supervisions in teachers and education support specialists. The successful education of children with ASD in a primary school of general education is also influenced by the preparedness of the child himself/herself to attend school. Adequate preparedness of a child with ASD for school should be associated with the development of elementary skills of self-management and appropriate behaviour, a positive attitude of the child to begin attending school, as well as the creation of opportunities for the child to get acquainted with the school’s environment and his/her teacher before starting to attend school. The study showed that, in order to achieve the successful education of the child, the cooperation between the parents and the school, which encompasses the parents’ activeness and their desire to cooperate with the school and the school’s desire to involve the parents in the process of the child’s education, is important. Attention to the child’s adaptation at school is one more important precondition for the successful education of a child with ASD. During the adaptation period, it is important that teachers, education support specialists and parents would cooperate closely, in order to assist the child to get acquainted with the school’s premises and to adapt them, as well as to organise the educational process while responding to the individual needs of a child with ASD. An important precondition for the successful education of the child at school is the creation of a favourable educational environment in the classroom, which in turn should be associated with the adaptation of the physical environment to the child’s needs, the creation of the psychosocial environment in the classroom community while maintaining positive relationships between the teacher and the child, between children and between parents and the attitude which is positive and oriented towards a child, as well as the cooperation between teachers and the child’s parents and other specialists and the expansion of the competences of the teacher to work with children with ASD.